Changes in soluble adhesion molecules in gingival crevicular fluid following periodontal surgery - KURU, LEYLA (AMER ACAD PERIODONTOLOGY, 2005)
Background: Inflammation of periodontal tissues during postoperative wound healing is mediated by cell surface adhesion molecules. Soluble forms of these antigens have also been identified and shown to be important in immunoregulatory processes, but have previously not been investigated during periodontal repair and regeneration. The present study has examined the presence and possible changes in soluble intercellular adhesion molecule-1 (sICAM-1; CD54) and lymphocyte function-associated antigen-3 (sLFA-3; CD8) in gingival crevical fluid (GCF) following periodontal surgery. Methods: GCF samples were collected from four groups: 1) a guided tissue regeneration (GTR) test; 2) a GTR control, at least one complete tooth unit away from the periodontal defect; 3) a conventional flap (CF) surgery; and 4) a crown lengthening (CL). Sandwich enzyme-linked immunosorbent assay (ELISA) was used to measure the levels of sICAM-1 and sLFA-3 in the GCF samples. Results: A marked increase in GCF volumes was found in all sites after surgery, although a persistent increase was associated only with the period of membrane retention at the GTR test sites. In addition, sICAM-1 and sLFA-3 were found in the GCF of healthy as well as diseased sites prior to treatment and the total amounts of both increased transiently following surgical intervention, especially sLFA-3. However, the concentrations of these GCF components, particularly sICAM-1, tended to decrease. Conclusions: The temporal decrease in the concentration of sICAM-1 and sLFA-3 in GCF may serve to enhance inflammatory reactions at surgically-treated periodontal sites, thereby limiting repair and regeneration in the periodontium. These soluble adhesion molecules may thereby be of potential therapeutic value and might also be useful markers for monitoring periodontal wound healing.
Keywords: cell adhesion molecules; gingival crevicular fluid; guided tissue; regeneration; lymphocyte function-associated antigen-3; periodontal diseases/therapy; periodontal regeneration; wound healing; GUIDED TISSUE REGENERATION; CELLS ADHERENT; HLA-DR; EXPRESSION; ICAM-1; FIBROBLASTS; LFA-3; FORMS; CYTOKINES; INVOLVEMENT